Calciprotein Particle Formation in Peritoneal Dialysis Effluent is Dependent on Dialysate Calcium Concentration. Issue 4 (July 2018) - Cai, Michael M.X.; Smith, Edward R.; Kent, Annette; Huang, Louis; Hewitson, Timothy D.; McMahon, Lawrence P.; Holt, Stephen G.
Background: The accumulation of fetuin-A-containing calciprotein particles (CPP) in the serum of patients with renal disease and those with chronic inflammation may be involved in driving sterile inflammation and extraosseous mineral deposition. We previously showed that both fetuin-A and CPP were present in the peritoneal dialysis (PD) effluent of stable PD patients. It is unknown whether different PD fluids might affect the formation of CPP in vivo. Method: Peritoneal effluent from 12 patients was collected after a 6-hour dwell with 7 different commercial PD fluids. Calciprotein particles and inflammatory cytokines were measured by flow cytometry. Results: High inter-subject variability in CPP concentration was observed. Peritoneal dialysis fluids containing 1.75 mmol/L calcium were associated with enhanced formation of CPP in vivo, compared with fluids containing 1.25 mmol/L calcium. Osmotic agent, fluid pH, and glucose concentration did not affect CPP formation. Peritoneal dialysis effluent CPP levels were not associated with changes in inflammatory cytokines. Conclusion: High calcium-containing PD fluids favor intraperitoneal CPP formation. This finding may have relevance for future PD fluid design.